GUIDANCE OF SELF ACHIEVEMENT VALUE IN DEVELOPING CIVIC DISPOSITION ON STUDENTS OF VOCATIONAL HIGH SCHOOL 3 TANGERANG - Dadang Sundawa, Sri Arusmiati, Endang Danial, (Department of Civic Education, 2014)
The impact of globalization is characterized competitive climate is a challenge for vocational competence in improving attitudes, knowledge, skills of graduates, it is a form of self-achievement. The value of self achievement SMK Negeri 3 Tangerang City fostered through the learning process and extracurricular Civics. This study used a qualitative approach to the case study method, the data obtained through interviews, observation, documentation studies. Planning and implementation of learning refers to the model Civics Curriculum 2013, the development-oriented attitude, knowledge, skills students proportionally. In extracurricular activities benefit the students change attitudes, knowledge, skills. Civics and learning through extracurricular activities can foster achievement scores in shaping the character of a good citizen.